Walory przyrodniczo-krajobrazowe gminy Bolesławiec = Natural and landscape values in the Bolesławiec region - Gawron, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents natural and landscape values in the Bolesławiec region. Author proposes chanse development of touristic infrastructure. Natural and landscape values should be protected. The moust important in the process of construction and operation of touristic infrastructure is protection of the environment.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)